Assessing the impact of 25-hydroxyvitamin concentrations on mortality in chronic diarrhea: a cross-sectional analysis - Li, Pengyu; Zou, Menglong; Peng, Ziming (Frontiers in Medicine, 2025)
BackgroundThe aim of this study was to assess the relationship between serum 25-hydroxyvitamin levels and all-cause mortality in patients with chronic diarrhea.MethodsWe carried out a cross-sectional study using information drawn from the National Health and Nutrition Examination Survey (NHANES). To assess mortality outcomes, we compared our data with records from the National Death Index as of December 31, 2011. The NHANES data were used to determine mortality outcome. We used a Cox regression model-based approach to analyze the relationship between serum 25-hydroxyvitamin concentrations and mortality in chronic diarrhea patients.ResultsA total of 2,972 participants with chronic diarrhea were included in our study, 488 cases of all-cause mortality were recorded. The study showed an L-shaped relationship between 25-hydroxyvitamin concentrations and all-cause mortality with a threshold of 73.40 nmol/L. On the left side of the threshold, each 1-unit increase in 25-hydroxyvitamin concentrations was associated with a 2.2% reduction in the risk of all-cause mortality (HR 0.978; 95% CI: 0.969, 0.987); however, on the right side of the threshold, there was no significant correlation between 25(OH)D concentrations and all-cause mortality.ConclusionSerum 25-hydroxyvitamin D levels showed an L-shaped association with all-cause mortality in patients with chronic diarrhea, with 73.40 nmol/L as the potential threshold. However, because this was a cross-sectional study, only an association, not a causal relationship, can be inferred. Further prospective studies are needed to confirm these findings and explore the potential impact of vitamin D supplementation on mortality outcomes.